ANALISIS PENERAPAN TARIF PEMOTONGAN PPH PASAL 21 TARIF PERATURAN PEMERINTAH NO. 58 TAHUN 2023 (Studi Komparatif di Yayasan Al-Fityan School Medan) - Pratiwi, Devi; Wibowo, M. Rizaldy; Tiara, Shita; Jayusman, Sri Fitria (UNIVERSITAS DHARMAWANGSA, 2025)
The objective of the research was to analyze the implementation of the Income Tax (PPh) Article 21 withholding rate in accordance with Government Regulation No. 58 of 2023 at Yayasan Al-Fityan School Medan. This regulation introduces the Average Effective Rate (TER) method to simplify income tax calculations for permanent employees. Although this regulation applies nationally, the foundation has not fully implemented the TER rate and still uses a progressive rate based on Article 17 of the HPP Law. The approach used in this research was descriptive qualitative, with data collected through interviews and documentation from the foundation's head of finance, treasurer, and financial staff. The analysis was conducted to assess administrative readiness, implementation challenges, and understanding of tax regulations. The research results indicate that the Average Effective Rate (TER) has not been implemented due to a lack of public awareness, human resources who do not understand the new provisions, and an inadequate payroll system. These findings indicate that although TER should simplify tax administration, its implementation still requires technical readiness and a good understanding from tax administrators. This research recommends that the foundation conduct training, evaluate payroll system, and develop internal policies in accordance with Government Regulation No. 58 of 2023. It is hoped that these results can serve as a reference for other non-profit educational institutions in responding to changes in tax policy.